Ethnopharmacy Study on the Use of Medicinal Plants in Lakawali Village, Malili District, East Luwu District (Padoe Tribes and Other Immigrant Tribes) - Edi Kamal, Sainal; Kadang, Yuniharce; Ananda, Febria (Politeknik Sandi Karsa, 2022)
Ethnopharmacy is a combination of disciplines that study the relationship between cultural habits in a community group in terms of its pharmaceutical side. This study aims to obtain information about the ethnopharmaceutical use of medicinal plants based on the types of medicinal plants part of the plant, the benefits of plants, processing methods and the use of medicinal plants used by the people of Lakawali Village, Malili District, East Luwu Regency. This type of research is descriptive observation. The sampling in this study used primary data obtained through interviews with 60 family heads of the people of Lakawli Village, Malili District, East Luwu Regency. The results of this study indicate that there are 33 types of medicinal plants divided into 26 families with 20 types of diseases. The most widely used plant as a medicine is Tappa Lorong/Brotowali which is efficacious as an ulcer medicine. Parts of plants used as medicine by the community include leaves, stems, fruits, flowers, bark, fruit skins, rhizomes, seeds, tubers. The most widely used plant part as medicine is the leaf with a percentage of 46%. The processing method and the use of medicinal plants by the community in Lakawali Village, Malili District, East Luwu Regency, are processed by boiling, pounding, squeezing, burning, and grating. And as for how to use it, namely by drinking, eating, making juice and affixed to the sick part.